2019
DOI: 10.1101/556852
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Novel polygenic risk score as a translational tool linking depression-related changes in the corticolimbic transcriptome with neural face processing and anhedonic symptoms

Abstract: Background: Convergent data from imaging and postmortem brain transcriptome studies implicate corticolimbic circuit (CLC) dysregulation in the pathophysiology of depression. To more directly bridge these lines of work, we generated a novel transcriptome-based polygenic risk score (T-PRS), capturing subtle shifts towards depression-like gene expression patterns. We then mapped this T-PRS onto CLC function and related depressive symptoms in a non-clinical sample of young adults. Methods: Genetic, self-report, an… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(13 citation statements)
references
References 62 publications
2
11
0
Order By: Relevance
“…To address this important gap, our group developed a novel transcriptome-based polygenic risk score (T-PRS) that makes use of common genetic variants to translate molecular changes observed in post-mortem tissue into an in-vivo peripheral proxy measure capturing similarity to the MDD cortical transcriptome. We recently mapped this score onto sex-specific patterns of CLC function in a non-clinical sample of young adults [8]. In this prior study, higher T-PRS was associated with elevated reactivity to emotional faces in men, but blunted reactivity to neutral faces in women.…”
Section: Introductionmentioning
confidence: 99%
“…To address this important gap, our group developed a novel transcriptome-based polygenic risk score (T-PRS) that makes use of common genetic variants to translate molecular changes observed in post-mortem tissue into an in-vivo peripheral proxy measure capturing similarity to the MDD cortical transcriptome. We recently mapped this score onto sex-specific patterns of CLC function in a non-clinical sample of young adults [8]. In this prior study, higher T-PRS was associated with elevated reactivity to emotional faces in men, but blunted reactivity to neutral faces in women.…”
Section: Introductionmentioning
confidence: 99%
“…These results provide an important initial validation of our approach and suggest a potential clinical relevance of the T-PRS. Of note, although we previously showed partially convergent effects of T-PRS and PRS derived from MDD genome-wide association studies (GWAS) on brain function phenotypes, we also showed that the scores are uncorrelated (4). The genes included in our T-PRS are also distinct from those emerging from transcriptome-wide association studies (TWAS) of depression, which seek to map MDD-associated SNPs onto specific gene expression patterns (24).…”
Section: Discussionmentioning
confidence: 61%
“…(A)Clusters in which T-PRS was negatively associated (1,2) or positively associated (3,4) with LGI in men.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations